Pengembangan Multimedia Pembelajaran Interaktif Berbasis Video terhadap Materi Sejarah Kebudayaan Islam Abu Bakar As Sh-Iddiq Sang Pembenar Kelas V Min 04 Trimo - Ulin Ni'am; Yuni Yuni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this research is to find out how Abu Bakar As-Siddiq, the fifth grade winner of MIN 04 Trimo Rejo creates interactive learning multimedia on SKI subjects by using video. Learning media must complement other learning components as part of the system. The aim is to facilitate learning activities as efficiently as possible. Abu Bakar As-Shiddiq, the fifth grade winner of MIN 04 Trimo Rejo, explains video-based interactive learning on SKI material in this post. The ADDIE model is used in this research. According to ADDIE, learning design creates learning through analysis, design, development, implementation, and evaluation phases. Learning system design development methodology is used to explain the research and development design process. Primary data collected through distributing questionnaires is the required data source. Participants in this study include media experts, material experts, and students. Nurul Huda University Sukaraja PGMI 6B students participated in this study. The interactive video is suitable for the application of learning, and the results of learning validation are rated as good.